Adjunctive antidepressant treatment among 763 outpatients with bipolar disorder: Findings from the Bipolar CHOICE and LiTMUS trials. Issue 2 (29th June 2020) - Köhler‐Forsberg, Ole; Sylvia, Louisa G.; Fung, Vicki; Overhage, Lindsay; Thase, Michael; Calabrese, Joseph R.; Deckersbach, Thilo; Tohen, Mauricio; Bowden, Charles L.; McInnis, Melvin; Kocsis, James H.; Friedman, Edward S.; et al.
Abstract: Background: Adjunctive antidepressants are frequently used for bipolar depression but their clinical efficacy has been studied in few trials and little is known about how co‐occurring manic symptoms affect treatment response. Methods: Bipolar Clinical Health Outcomes Initiative in Comparative Effectiveness ( N = 482) and Lithium Treatment Moderate‐Dose Use Study ( N = 281) were similar comparative effectiveness trials on outpatients with bipolar disorder comparing four different randomized treatment arms with adjunctive personalized guideline‐based treatment for 24 weeks. Adjunctive antidepressant treatment could be used if clinically indicated and was assessed at every study visit. Adjusted mixed effects linear regression analyses compared users of antidepressants to nonusers overall and in different subcohorts. Results: Of the 763 patients, 282 (37.0%) used antidepressant drugs during the study. Antidepressant users had less improvement compared to nonusers on the Clinical Global Impression Scale for Bipolar Disorder and on measures of depression. This was particularly true among patients with co‐occurring manic symptoms. Exclusion of individuals begun on antidepressants late in the study (potentially due to overall worse response) resulted in no differences between users and nonusers. We found no differences in treatment effects on mania scales. Conclusions: In this large cohort of outpatients with bipolar disorder, clinically indicated and guideline‐based adjunctive antidepressant treatment was not associated with lower depressive symptoms or higher mania symptoms. The treatment‐by‐indication confounding due to the nonrandomized design of the trials complicates causal interpretations, but no analyses indicated better treatment effects of adjunctive antidepressants.